Twelve-pulse rectifiers in power supply system of urban electric transport aleva - E. Yu. Salita; T. V. Kovaleva (Омский научный вестник)
The introduction of twelve-pulse rectifiers instead of six-pulse ones at traction substations of urban electric transport leads to an increase in technical and economic indicators, energy savings, a decrease in leakage current. These result in electrical safety of passengers, a trolleybus driver and depot maintenance personnel. Twelve-pulse rectifiers can have a serial or parallel connection of sixpulse bridges. With a parallel circuit, it is necessary to have an equalizing reactor. The implementation of a twelvepulse serial type rectification scheme can be carried out by industrial development by manufacturers of new dry converter transformers with different typical power and new rectifiers (blocks). As part of the new rectifiers, it is necessary to have tablet avalanche valves with coolers based on heat pipes due to their advantages over nonavalanche valves.